IDENTIFIKASI MODEL KOMUNIKASI HUPMAS PT PERTAMINA (PERSERO) DALAM MEMBINA MEDIA RELATIONS (Lembaga Penerbitan Universitas Esa Unggul, 2008)
AbstractThis study aims to identify the model of communication Hupmas PT. Pertamina (Persero) in fostering relations with the media using the case study method (casestudy). Researchers used the theory of James E. Grunig model to answer what the dominant communications conducted by Pertamina for building Hupmas media relations. From the results of this study the researchers conducted through analysis of primary and secondary data can be concluded that the dominant communication model implemented Hupmas Pertamina for media relations is to foster communication model Two-way Symmetric and Public Information, while the communication model and Agentry Press Two-way Asymmetric still applied but only use certain characteristics. Keywords: Model of Communication, Media Relations, TheoryJames E. Grunig